Applying High-Resolution Variant Classification to Cardiac Arrhythmogenic Gene Testing in a Demographically Diverse Cohort of Sudden Unexplained Deaths. (December 2017) - Lin, Ying; Williams, Nori; Wang, Dawei; Coetzee, William; Zhou, Bo; Eng, Lucy S.; Um, Sung Yon; Bao, Ruijun; Devinsky, Orrin; McDonald, Thomas V.; Sampson, Barbara A.; Tang, Yingying
Abstract : Background—: Genetic variant interpretation contributes to testing yield differences reported for sudden unexplained death. Adapting a high-resolution variant interpretation framework, which considers disease prevalence, reduced penetrance, genetic heterogeneity, and allelic contribution to determine the maximum tolerated allele count in gnomAD, we report an evaluation of cardiac channelopathy and cardiomyopathy genes in a large, demographically diverse sudden unexplained death cohort that underwent thorough investigation in the United States' largest medical examiner's office. Methods and Results—: The cohort has 296 decedents: 147 Blacks, 64 Hispanics, 49 Whites, 22 Asians, and 14 mixed ethnicities; 142 infants (1 to 11 months), 39 children (1 to 17 years), 74 young adults (18 to 34 years), and 41 adults (35 to 55 years). Eighty-nine cardiac disease genes were evaluated. Using a high-resolution variant interpretation workflow, we classified 17 variants as pathogenic or likely pathogenic (2 of which were incidental findings and excluded in testing yield analysis), 46 novel variants of uncertain significance, and 130 variants of uncertain significance. Nine pathogenic or likely pathogenic variants in ClinVar were reclassified to likely benign and excluded in testing yield analysis. The yields of positive cases by ethnicity and age were 21.4% in mixed ethnicities, 10.2% Whites, 4.5% Asians, 3.1% Hispanics, and 2% Blacks; 7.7% children, 7.3% in adults, 5.4% young adults, and 2.8% infants. The percentages of uncertain cases with variants of uncertain significance by ethnicity were 45.5% in Asians, 45.3% Hispanics, 44.20% Blacks, 36.7% Whites, and 14.3% in mixed ethnicities. Conclusions—: High-resolution variant interpretation provides diagnostic accuracy and healthcare efficiency. Under-represented populations warrant greater inclusion in future studies. Abstract : Supplemental Digital Content is available in the text.